Fachkräfte im Bereich der Medienpädagogik an Öffentlichen Bibliotheken in Deutschland: Anforderungen und Aufgaben - Petter, Lioba; Deutsch, Deutsch (o-bib. Das offene Bibliotheksjournal / Herausgeber VDB, 2023)
The article presents the results of a Bachelor’s thesis in which the expectations of public libraries towards applicants for media education positions were examined with regard to the intended tasks and required competences. Also considered were the reasons for advertising vacancies in a non-specialized way as well as the assessment of employees who already work in media education in public libraries. The data basis of the study consisted of full texts of job advertisements on the OpenBiblioJobs platform and the mailing list InetBib in the period under investigation from 2016 to 2021. In addition, qualitative interviews were conducted with professionals in the field of media education as well as library managers.
Keywords: Public libraries; Media pedagogy